The meritocracy trap: Early childhood education policies promote individual achievement far more than social cohesion - Katarzyna Bobrowicz; Pablo Gracia; Ziwen Teuber; Samuel Greiff (PLoS ONE, 2025)
Governments worldwide have reformed early childhood education (ECE) to equip young people with competitive skills for an increasingly specialized workforce. These reforms have coincided with a widespread acceptance of meritocratic beliefs holding that talent and effort, rather than uncontrollable factors (e.g., luck, social context), determine individuals’ lifetime success and achievement. This study examines whether recent ECE reforms may have promoted an economic meritocratic mindset that favors skills linked to individual competition for future achievement. Data came from a total of 92 documents published between 1999 and 2023, including ECE advisory reports from international organizations and government-endorsed ECE curricula from 53 countries across Africa, the Americas, Asia, Europe, and Oceania. A step-by-step thematic analysis was conducted through combining qualitative text coding with statistical analyses applied to the emerging themes. Findings show that: (1) while experts and policymakers recognized the importance of ECE access and quality, they defined social cohesion primarily through economic indicators; (2) ECE documents prioritized cognitive skills and –mostly among international organizations– socioemotional skills as key for individual achievement, but citizenship skills were largely omitted; (3) individual agency and responsibility within ECE contexts were defined as central to educational and lifetime success, while uncontrollable factors (e.g., intergenerational transmission of advantage, family origin) were largely neglected; (4) both international organizations and governments strongly embraced an economic meritocratic mindset in ECE, implying that life outcomes mainly depend on talent and effort, obscuring the role of support and solidarity from peers, relatives, communities or institutions. Overall, this study suggests that ECE reforms have globally reinforced the pitfalls of meritocracy by promoting educational policies that prioritize competition over cooperation, individualism over solidarity, and the widespread notion that talent and effort, rather than uncontrollable factors such as luck or social context, determine individuals’ lifetime success in society.